Clinical and Infective Outcome of Parasitologicaly Confirmed Kala-Azar Patients Treated with Sodium Antimony Gluconate (Journal of Medicine, 2010)
A total of fifty consecutive cases of Kala-azar admitted in the medicine units of Rajshahi Medical College Hospital during the period from February 2006 to October 2006 were included in this study. The number of the patients clearly indicates that the burden of Kala-azar in this region is significant and expanding. Male to female ratio was 1.9:1. Fever (96%) and splenomegaly (100%) were the predominant features. Hepatomegaly was found in 82% of the cases. Other clinical manifestations were Hyperpigmentation (76%), weight loss (62%), pallor (60%), jaundice (10%), oedema (10%), cough (6%) and lymphadenopathy (4%). Fever of 75% cases subsided within one week of starting treatment. Weight of 89.6% cases increased after completion of treatment. After completion of treatment spleen size regressed in 95.8% cases and no LD (Leishmania donovani) body was seen in 46 (92%) patients splenic / bone marrow aspiration after completion of treatment. 2 (4%) patients remain LD body positive after completion of treatment and 2 (4%) patients died during treatment. Still sodium antimony gluconate (SAG) is very effective in the clinical and parasitologicaly confirmed Kala-azar patients. A combination of sand fly control, early detection and treatment of the patients is the best approach for controlling Kala-azar. Keyword: Kala-azar, Sodium Stibogluconate, LD (Leishmania donovani) body, splenic or bone marrow aspiration. DOI:10.3329/jom.v11i1.4261 J Medicine 2010: 11: 12-16